Particularized protection: UNSC mandates and the protection of civilians in armed conflict. Issue 2 (14th March 2016) - Shesterinina, Anastasia; Job, Brian L.
ABSTRACT: The protection of civilians at risk in armed conflict has, since the late 1990s, become institutionalized at the United Nations (UN), gaining acceptance as a normative rationale for UN peacekeeping. However, the bulk of civilians in need of protection in armed conflict are unlikely to attain it. The article develops an argument on 'particularized protection' – particularized in that UN Security Council (SC) mandates are formulated and adjusted over time to direct mission protection to specific subsets of civilian populations, that is, those relevant to the UN itself, the host state, other states, NGOs and the media, leaving most local civilians receiving little effective protection. Particularized protection, we argue, is a result of the institutional dynamics involving actors producing mandates – the UNSC – and those providing protection – peacekeeping missions – whereby mandates are specified to direct mission protection to selected, particularized groups. We demonstrate these dynamics in two cases, Côte d'Ivoire and Somalia.